A Review of Modern Isotope Applications in Engineering Hydrology - Bruska S. Mamand; Dana K. Mawlood (Zanco Journal of Pure and Applied Sciences, 2023)
Climate change can affect water systems in general by varying rainfall quantities and distribution, increasing air and water temperatures, and eventually affecting groundwater sources. Hydrology is a water science of studying the occurrence and distribution of water on the planet and in its atmosphere. In this regard, isotope technology has arisen as an effective scientific approach for addressing water-related concerns such as groundwater recharging, process improvement, surface water research, salinization and pollution investigations, and so on. The current paper emphasizes the importance of isotope technology and applications for water management in changing climatic conditions by reviewing a series of publications including four investigations in Kurdistan region of Iraq and eight other studies at (California, China, Romania and Taiwan) that focus on the variation of oxygen-18 and deuterium isotopic concentrations, as well as the various factors that influence them. Also, the methods of estimating the dwell time of groundwater in an aquifer by using stable isotope behind the dating criteria with radioactive carbon and tritium in water molecules.